Regional Goods Management in Supporting Activity Planning at the Regional Secretariat of Merangin District - Eryasi Daryati; Dedi Epriadi (Yayasan Adra Karima Hubbi, 2023)
Background. The existence of assets at this time gave birth to a paradox in terms of efforts to increase income (PAD). As a result, the great potential that lies ahead is not optimally explored. Instead they found any source of PAD results to be uncertain. Purpose. Assets should be very large areas that are better managed so as to produce optimal profits. It would be nice if the Regional Head from the Regent, Mayor, to the Governor when he is appointed immediately recognizes and understands the exact condition of the assets and then reports back to the community periodically. Method. In this study, researchers used a qualitative descriptive approach. Taking the location which is located in Merangin Regency, Jambi Province with a total sample of 18 people. In carrying out the research conducted using several data collection techniques including interviews, observation, questionnaires. Results. Problems related to the management of goods are also urgent but can still be handled ideally, including at the Secretariat General of the Merangin District Section. Based on the researchers' observations, there are several fundamental problems that have caused the management of goods to not operate effectively and can be used as indicators to support planning activities at the Regional Secretariat Section of Merangin Regency. Goods Management in Support of the General Plan of Activities in Merangin Regency Regional Assets and are still not optimal. Conclusion. Efforts made to overcome obstacles in the Management of Goods in support of activity planning in the Regional Secretariat Section are to improve the technical capabilities of existing personnel management goods, maximize the management of goods to and encourage the process of internal control mechanisms in the General Section to maximize the management of regional property in supporting activities planning.